AKTIVITAS ANTIBAKTERI KURKUMIN DAN KOMPLEKS TEMBAGA (II) KURKUMIN TERHADAP S.AUREUS DAN E.COLI - Firdaus, Giska Ristianty; Silalahi, Imelda Hotmarisi; Ardiningsih, Puji (Tanjungpura University, 2024)
Copper (II) complex of curcumin was prepared from the reaction between curcumin and a metal precursor (CuCl2.2H2O) in ethanol with a mole ratio curcumin to metal 2:1. The FTIR spectrum of Cu2+-curcumin shows a change in the absorption band and a shift in the wave number, especially in the absorption band of the phenolic